Stigmatized Asset Value: Is It Temporary or Long-Term? - McCluskey, Jill J.; Rausser, Gordon C. (The Review of Economics and Statistics, 2003)
Stigma is a negative attribute of real estate acquired by environmental contamination and reflected in its value (Elliot-Jones, 1996). Using a model of neighborhood turnover with external economies, we show that both temporary stigma and long-term stigma are possible equilibrium outcomes after the discovery and cleanup of a hazardous waste site. The existence and duration of stigma are examined using hedonic price techniques with data from housing sales prices in Dallas County, Texas. We find that results depend critically on distance from the hazardous waste site. Neighborhood turnover due to changes in the level of poverty also appears likely.